Colony Stimulating Factors in Early Feline Infectious Peritonitis Virus Infection of Monocytes and in End Stage Feline Infectious Peritonitis; A Combined In Vivo and In Vitro Approach - Malbon, Alexandra J. (Pathogens, 2020)
Feline coronavirus (FCoV) infection initiates monocyte-associated viremia and viral persistence. Virus-infected, -activated monocytes also trigger feline infectious peritonitis (FIP), a fatal systemic disease of felids typified by granulomatous (peri)phlebitis. Currently, the exact mechanisms inducing monocyte activation and FIP are unknown. This study attempted to identify the potential immediate effect of virulent FCoV on colony-stimulating factor (CSF) (granulocyte (G)-CSF, monocyte (M)-CSF and granulocyte-monocyte (GM)-CSF levels through in vitro assessment, alongside prototypical pro- and anti-inflammatory mediators (interleukin (IL)-1, IL-6, IL-12p40, tumor necrosis factor (TNF)-α, and IL-10); this was assessed alongside the in vivo situation in the hemolymphatic tissues of cats euthanized with natural end-stage FIP. For the in vitro work, isolated monocytes from SPF cats were cultured short-term and infected with the FIP virus (FIPV) strain DF2. Mediator transcription was assessed by quantitative reverse transcriptase PCR (RT-qPCR) at 3, 6 and 9 h post infection (hpi), and in the post-mortem samples of bone marrow, spleen, and mesenteric lymph nodes (MLN) of cats with FIP. We observed limited and transient changes in cytokine transcription in monocytes after infection, i.e., a significant increase of IL-6 at 3 hpi and of GM-CSF over the 3 and 6 hpi period, whereas M-CSF was significantly decreased at 9 hpi, with a limited effect of age. The findings indicate that the infection induces expansion of the monocyte/macrophage population, which would ensure the sufficient supply of cells for consistent viral replication. In natural disease, the only upregulation was of G-CSF in the MLN, suggesting either immune exhaustion or an active downregulation by the host as part of its viral response.